Foliar Phosphorus Boosts the Antioxidant Defenses and Yield of Off-Season Corn Under Water-Stress - de Souza, Fernanda Marcolan [UNESP]; Galeriani, Tatiani Mayara [UNESP]; Moretti, Luiz Gustavo [UNESP]; Viveiros, Josiane [UNESP]; Rodrigues, Vitor Alves [UNESP]; de Oliveira, Sirlene Lopes [UNESP]; de Campos, Murilo [UNESP]; Portugal, José Roberto [UNESP]; Bossolani, João William [UNESP]; Crusciol, Carlos Alexandre Costa [UNESP] (Springer Nature, 2025)
The yields of second crop (off-season) corn is often limited by mild temperature and prolonged periods of low water availability. This study evaluated the ability of foliar application of phosphorus (P) at different phenological stages (V4, V6, V8 and R1) over two growing seasons (2021 and 2022) in improving plant performance under these adverse conditions. To test this, we assessed nutrient concentrations, the activity of key photosynthetic enzymes such as phosphoenolpyruvate carboxylase (PEPcase) and Ribulose-1,5-bisphosphate carboxylase/ oxygenase (RuBisCO), photosynthetic performance, oxidative stress markers, antioxidant enzyme activities, grain production, and overall yield. Foliar P application improved physiological and biochemical responses in second-crop corn. Across both years, chlorophyll a content and net photosynthesis increased by 10.8% and 11.8%, respectively. In 2022, chlorophyll b content rose by 12.3%, while in 2021, stomatal conductance and water use efficiency improved by 5.6% and 10.4%, respectively. Grain yield increased by an average of 12.1%. Conversely, foliar P application reduced leaf hydrogen peroxide (-18.5%) and lipid peroxidation (-18.0), as well as the activities of antioxidant enzymes, including superoxide dismutase (-6.7%), catalase (-58.1% in 2022), and ascorbate peroxidase (-38.6% in 2022). Phosphorus application at V8 and R1 stages proved most effective in mitigating oxidative stress. These findings demonstrate the potential of foliar P supplementation to enhance plant metabolism and significantly improve grain yield in second-crop corn, offering a practical strategy to mitigate abiotic stress under off-season growing conditions.